Short- Term Memory of Quran Hafizat and non- Hafizat; from female students of human colleges at King Saud University (a comparative study) - Almanie, Sarah Ibrahim; Moawad, Ruba Abdelmatloub (Journal of Educational and Psychological Sciences, 2020)
This study aimed to investigate the differences in Short- Term Memory (STM) between Quran Hafizat (Memorized the Holly Quran) and Non- Hafizat University female students. We hypothesized that Quran Hafizat will perform better on the STM tasks than Non- Hafizat We followed the comparative causal method in this research, 40 female students participated in this study, and were divided into two groups, 20 Quran Hafizat and 20 Non Hafizat, they ranged in age between 19- 24 years old. We used the STM auditory and visual Test (direct & delayed), and it comprise of 11 subtests. In general, the results indicated no differences in STM between the two groups, except on one subtest.* The authors extend their appreciation to the Deanship of Scientific Research, King Saud University for funding this work through the Undergraduate Research Support Program.
Keywords: Short term memory; Auditory memory; Visual Memory; Quran Hafizat; Quran Hafizat and Non- Hafizat